ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PEMILIHAN KONSERVATISME AKUNTANSI - Angga Alfian; Arifin Sabeni (Diponegoro Journal of Accounting, 2013)
The main focus in the financial statements is income information and one of the principles relating to financial statements and income information is accounting conservatism, namely an act carefully in determining the amount of the profit. Some sides supported the need for the principle of conservatism because can neutralize the attitude of optimism the company manager. Other side rejected the use of accounting conservatism principle because the results tend to be biased and does not reflect the company's actual financial situation. This research aims to analyze the factors which influence on the selection of accounting conservatism. The research sample is a manufacturing company which is listed on the Indonesia stock exchange (BEI) in 2009-2011. The research results indicate some of the factors that influence significantly to selection of accounting conservatism, such as leverage, capital intensity ratio and growth opportunity. And other factors, such as the size of the company, managerial ownership and public ownership has no significant effect for the selection of accounting conservatism.